Dov Levitte and Yosef Garfinkel, A Diorite New Kingdom Scarab from Tel Lachish - Brandl, Baruch (Ägypten und Levante, 2020)
This paper presents a rare scarab made of diorite and set in a golden bezel that was excavated in a topsoil locus at Tel Lachish. Although it lacks a clear stratigraphic context, the scarab still presents important data on the Late Bronze Age at Lachishnull